Numerical study on hydrodynamic characteristics of a submersible floating offshore wind turbine integrated with an aquaculture cage - Peng Xu; Jing Xu; Yuan Zhang; Changqing Jiang; Zhaode Zhang; Zhanbin Meng (Frontiers in Marine Science)
The increasing global need for renewable energy has rendered the development of offshore wind energy extremely significant. In areas where ocean depths exceed 50 meters, conventional permanent foundations become economically unfeasible, becoming floating offshore wind turbines (FOWTs) a superior alternative. Simultaneously, the development of marine resources in offshore areas has failed to meet increasing market demand, necessitating the urgent expansion of aquaculture fisheries into deeper waters. This research developed a fully integrated model of a cage platform, net system, and mooring system, compatible with the NREL 5MW wind turbine. Numerical simulation methods, based on potential flow theory and Morrison’s equation, are utilized to examine the motion response characteristics of the coupled system under various sea conditions. The study results demonstrate that the net, acting as a damping element, significantly decreased the system’s motion response and enhanced its stability. The system’s dynamic response is influenced by wave height and period in both regular and irregular wave circumstances, particularly under extreme sea conditions. Furthermore, the net’s presence minimally affects the wind turbine’s power output while contributing to the mitigation of power fluctuations. The examination of complex environmental circumstances influenced by wind, waves, and currents reveals that a rise in current velocity markedly changes the system’s surge motion trend, although it has little impact on power output. The work establishes a theoretical framework for the design and optimization of deep-sea wind-fishery integrated systems, providing insights into the maximization of marine resource utilization and the commercial deployment of wind energy.